Metabolomic Analysis of Perfusate During Hypothermic Machine Perfusion of Human Cadaveric Kidneys. Issue 4 (April 2015) - Guy, Alison J.; Nath, Jay; Cobbold, Mark; Ludwig, Christian; Tennant, Daniel A.; Inston, Nicholas G.; Ready, Andrew R.
<x xml:space="preserve">Abstract</x> Background The metabolic processes occurring within the preserved kidney during hypothermic machine perfusion (HMP) are not well characterized. The aim of this study was to use nuclear magnetic resonance (NMR) spectroscopy to examine the metabolomic profile of HMP perfusate from human cadaveric kidneys awaiting transplantation and to identify possible discriminators between the profiles of kidneys with delayed graft function (DGF) and immediate graft function (IGF). Methods Perfusates from HMP kidneys were sampled at 45 min and 4 hr of preservation with the LifePort Kidney Transporter 1.0 (Organ Recovery Systems, Chicago, IL) using KPS-1. Prepared samples underwent 1-D Proton-NMR spectroscopy, and resultant spectra were analyzed. Clinical parameters were collected prospectively. Results Perfusate of 26 transplanted cadaveric kidneys was analyzed; 19(73%) with IGF and 7(27%) with DGF. Glucose concentrations were significantly lower in DGF kidneys compared to those with IGF at both 45 min (7.772 vs. 9.459 mM, P = 0.006) and 4 hr (8.202 vs. 10.235 mM, P = 0.003). Concentrations of inosine and leucine were significantly different between DGF and IGF kidneys at 45 min (0.002 vs. 0.013 mM, P = 0.009 and 0.011 vs. 0.006 mM, P = 0.036), and gluconate levels were also significantly different between DGF and IGF kidneys at 4 hr (49.099 vs. 59.513 mM, P = 0.009). Conclusion Significant metabolic activity may be occurring in kidneys during HMP. The NMR spectroscopy of the perfusate can identify differences in the metabolomic profiles of DGF and IGF kidneys that might have a predictive role in viability assessment. Modification of harmful metabolic processes may improve outcomes for HMP kidneys.